Uwarunkowania historyczne roli i statusu języka polskiego w systemie edukacji w Galicji 1. połowy XIX wieku - Zimmermann, Peter (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
During the partitions of Poland in 1772, 1795 and 1815 its southern part was annexed by the Habsburg Monarchy and integrated into the Austrian Empire as the Kingdom of Galicia and Lodomeria. Till the end of World War I the inhabitants of Galicia were citizens of the Austrian Empire and their lives were influenced by the political and social ideology of the Austrian government. One of the most significant changes were connected to the language issue. Austrian or German-speaking officials came to Galicia and so did German as it became the main administrative language. This was also the case for the Austrian education system, which mainly focused on teaching German language as they wanted to integrate the multilingual and multicultural inhabitants of the Austrian Empire under the leadership of the Austrian rulers. This article deals with the issue how the Austrian education system influenced the development and understanding of national consciousness of the Polish population in Galicia in the first half of the 19th century by analysing which role the Polish language played in the primary and secondary school system. This period is important because it shows the main intentions of the Austrian educational system and also because the first important School Laws were passed, which influenced the education system in Galicia for over half the century. This article is structured in two parts. The first part contains an analysis of the most important School Laws. The aim is to show the intentions and the ideology which guided the Austrian government in creating the education system and to analyse which role the Polish language played in it. The second part deals with the actual effects of the Austrian education policy for the young Polish generations of Galicia. This will allow a more realistic interpretation of the influence the education system in Galicia had on building or suppressing the development of a Polish national consciousness. This part includes analyses of school statistics and most importantly memories from schooldays from former Galician school children which gives an inside on the role the Polish language played in the school and in their own lives.